2016
DOI: 10.1002/2015jb012416
|View full text |Cite
|
Sign up to set email alerts
|

Seismic reflection imaging of the Juan de Fuca plate from ridge to trench: New constraints on the distribution of faulting and evolution of the crust prior to subduction

Abstract: We present prestack time‐migrated multichannel seismic images along two cross‐plate transects from the Juan de Fuca (JdF) Ridge to the Cascadia deformation front (DF) offshore Oregon and Washington from which we characterize crustal structure, distribution and extent of faults across the plate interior as the crust ages and near the DF in response to subduction bending. Within the plate interior, we observe numerous small offset faults in the sediment section beginning 50–70 km from the ridge axis with sparse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
197
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(215 citation statements)
references
References 108 publications
(186 reference statements)
12
197
3
Order By: Relevance
“…A region-byregion comparison of the influence from underthrust sediments and incoming plate deformation on possible near-plate-interface seismicity is shown in Table 2. In this region, the incoming JdF is also less deformed than in its southern portion; the top of the oceanic crust is comparatively smooth with relief less than 150 m (Canales et al, 2017;Han et al, 2016). The relative scarcity of earthquakes on the plate interface offshore Washington mirrors the lack of interface seismicity observed off Vancouver Island during the (Obana et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…A region-byregion comparison of the influence from underthrust sediments and incoming plate deformation on possible near-plate-interface seismicity is shown in Table 2. In this region, the incoming JdF is also less deformed than in its southern portion; the top of the oceanic crust is comparatively smooth with relief less than 150 m (Canales et al, 2017;Han et al, 2016). The relative scarcity of earthquakes on the plate interface offshore Washington mirrors the lack of interface seismicity observed off Vancouver Island during the (Obana et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have revealed faults within the sediment section blanketing the JdF plate at distances of up to 200 km west of the deformation front (Figure c) and one region of crustal‐scale faulting [ Nedimović et al ., ]. Reflection images derived from the collocated MCS data acquired along our Oregon transect presented in Han et al [] reveal faults within the sediments and faint fault reflections in the upper crust at distances up to 320 km seaward of the deformation front. Sediment and crustal faults are sparse and heterogeneous in distribution west of 130–140 km from the deformation front, but increase in density at closer distances, with numerous faults within the sediments and crust at distances <130 km, as well as a prominent group of ridgeward dipping lower crustal reflectors (LCRs) found 70–150 km from the deformation front (Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…The zone of deep‐penetrating faults falls within the region of increasing mantle velocities immediately to the east of the small propagator. Mantle water contents of <1 wt % (Figure c) are estimated for this region, consistent with values reported by Han et al [] based on estimates of the volume of the imaged fault zones. There is no clear explanation for why, within 15 km of the deformation front, our mantle velocities reach predicted dry values (Figure c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to determine if the top of the JdF crust disappears below 40-km depth or simply decreases in S velocity contrast with the overlying mantle to noise levels. The resulting depth of the JdF Moho beneath MSH is 74 km, placing the slab surface at 68 km beneath MSH assuming a JdF crustal thickness of 6 km as seen offshore (Han et al, 2016). The resulting depth of the JdF Moho beneath MSH is 74 km, placing the slab surface at 68 km beneath MSH assuming a JdF crustal thickness of 6 km as seen offshore (Han et al, 2016).…”
Section: Two-dimensional Migration Imagesmentioning
confidence: 99%